Scanning Electron Microscopic Investigation of the Eviscerated Strands of Perhentian Island Bohadschia spp - Mohsin, S. S. J.; Nik Norliza, N. H.; Nik Fakurudin, N. A.; Jamaruddin, M. A.; Ismail, A. A.; Wan Rosli, W. I. (Microscopy Society of Singapore, 2012)
As a defense reaction, the species Bohadschia grafeii and probably also another species, which we temporarily named as Bohadschia spp., eviscerate plenty of noodle-like threads which stick to the intruder’s body. These species belonging to the order holothuridae, are also known as ‘timun laut kuning’ and ‘timun laut batik’ amongst the local populace at the resort islands of Perhentian, Terangganu, Malaysia. The eviscerated materials are probably collagen-based materials exhibiting unique features when observed under the scanning electron microscope (SEM). The threads, measuring 0.3 to 2.5 mm in diameter with variable length are white in colour, shiny and are sticky in nature. Under the SEM, the features which confer the ability for the threads to stick to many different types of surfaces are clearly displayed. The presence of cup-like structures distributed along the threads do provide possible explanation of the possible vacuum suctional ability that makes the threads stick fast to almost any surface. The role of this defense system, at least in the two species mentioned here, has not been described earlier.